(untitled) (Journal of National Institute of Ophthalmology, 2026)
Introduction: Patients satisfaction regarding medical care organizations like tertiary care hospital is important in the provision of services to patients. Patient satisfaction is a measure of how happy a patient is with their healthcare. Although “patient satisfaction” and “patient experience” are sometimes used interchangeably, they’re actually two separate concepts. This effort has a positive impact on health and education sector in Bangladesh. Every year the demand of health care is increasing and health sector facing difficulties to maintaining the principle of high-quality health care delivery system. Objective: To analyze the level of satisfaction of patients attending the eye department of National institute of ophthalmology & Hospital, utilize the hospital service and determine the factors related to their satisfaction. Methodology: The present study was descriptive, cross sectional carried out in the outdoor, indoor and emergency of National institute of Ophthalmology Hospital, Dhaka from January 2021 to July 2021. Quantitative data has been collected. A sample population 384 patient using random sampling technique through face-to-face interview by using pretested semi structured questionnaire. The An ethical approval was obtained from the North South university public health department. Result: The patients were asked to evaluate the overall performance of the hospital. The majority (60.5%) said average and 39.5% said good. Conclusion: the patient satisfaction is very important to increase the flow of patient and reduce the burden of eye related service. Quality of care, doctor and staff attitude and behavior need to improve to enhance the satisfaction level of patient. Hospital general hygiene facility also need to improve. J.Natl.Inst.Ophthalmol.2024;7(2): 39-46